(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article examines the historical metamorphosis of Uzbek folk attire, tracing its evolution from ancient origins to its establishment as a potent symbol of national identity. The study positions traditional clothing as an integral element of material and spiritual culture, reflecting a people’s ethnic history, social relations, aesthetic norms, and intercultural exchanges. The analysis begins with the earliest evidence of clothing from the Mesolithic period, as seen in the Zarautsoy rock paintings, and progresses through significant historical epochs, including the Achaemenid period. The research pays particular attention to the pivotal transformations of the late 19th and early 20th centuries, highlighting influences from RussianEuropean culture and their impact on garment cuts and fabrics. The article concludes that Uzbek folk costume is not merely a utilitarian object but a dynamic, evolving system whose form, ornamentation, and function are shaped by a complex interplay of historical, socio-economic, and human factors, ultimately crystallizing into a marker of cultural heritage and national consciousness